Quesungual slash and mulch agroforestry system improves rain water productivity in hillside agroecosystems of the sub-humid tropics - Castro, Aracely; Rivera Peña, Mariela; Ferreira, Oscar; Pavón Tijerino, Jellin del Carmen; García, Edwin; Amézquita Collazos, Edgar; Ayarza, Miguel Angel; Barrios, Edmundo; Rondón, Marco Antonio; Pauli, Natasha; Baltodano, Maria Eugenia; Mendoza, Bismark; et al. (CGIAR Challenge Program on Water and Food, 2009)
The Quesungual Slash and Mulch Agroforestry System (QSMAS) is a smallholder production system with a group of technologies for the sustainable management of water, soil and nutrient resources in drought‐ prone areas of hillside agroecosystems of the sub‐humid tropics. QSMAS integrates local and technical knowledge and provides resource‐poor farmers with an alternative to the environmentally unfriendly slash and burn (SB) traditional production system. The main objective of this study was to determine the key principles behind the biophysical resilience of QSMAS and its capacity to sustain crop production and alleviate water deficits on steeper slopes with risk of soil erosion. Activities included the evaluation of QSMAS performance compared to the traditional SB system in terms of water dynamics (including crop water productivity), nutrient dynamics, and greenhouse gas fluxes (including global warming potential). Results indicate that the application of the four principles behind QSMAS productivity and sustainability (no slash‐and‐burn, permanent soil cover, minimal disturbance of soil, and improved fertilizer practice), has positive effects on the soil‐plant‐ atmosphere relationships, soil quality, and on landscapes and the environment. Validation in Nicaragua and Colombia underpin the potential of QSMAS to enhance support for livelihoods in vulnerable rural areas in sub‐humid tropics.